Some experiments with the U.S.A. Standard Evaporimeter - VENKITESHWARAN, S. P.; JAGANNATHAN, P.; RAMAKRISHNAN, S. S. (MAUSAM, 1959)
The U.S.A. Standard Evaporimeter is in regular usc at a number of selected Agricultural Farms in the Indian States and in the Observatories of the India Meteorological Department . The evaporimeter consist. of a cylindrical reservoir 48” in diameter and 10” high supported on a wooden frame 4” high.